2008
DOI: 10.1007/s00431-007-0646-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of very low birthweight infants after introducing a new standard regime with the early use of nasal CPAP

Abstract: In this paper, a retrospective study was performed to find out whether the introduction of early nasal continuous positive airway pressure (nCPAP) as a new standard regime of very low birthweight infants will lead to a decreasing tracheal intubation and ventilation rate, as well as to a lower incidence of bronchopulmonary dysplasia in a tertiary-level perinatal centre. Ninety-three infants (study group) with early nCPAP as the first respiratory support were compared to 63 infants (historical control group) bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Compared to non-EnCPAP neonates, EnCPAP neonates had reduced mortality, mechanical ventilation, BPD and PH, without an increased risk of pneumothorax. The lower rates of endotracheal intubation at birth and surfactant therapy despite more RDS in our EnCPAP neonates were similar to those reported by others [13,14,15,16,17,18,19,20,21]. Contrary to studies reported elsewhere, our EnCPAP neonates had a significantly lower mortality at discharge [3,4,22] and no increased risk of IVH [22].…”
Section: Discussioncontrasting
confidence: 57%
“…Compared to non-EnCPAP neonates, EnCPAP neonates had reduced mortality, mechanical ventilation, BPD and PH, without an increased risk of pneumothorax. The lower rates of endotracheal intubation at birth and surfactant therapy despite more RDS in our EnCPAP neonates were similar to those reported by others [13,14,15,16,17,18,19,20,21]. Contrary to studies reported elsewhere, our EnCPAP neonates had a significantly lower mortality at discharge [3,4,22] and no increased risk of IVH [22].…”
Section: Discussioncontrasting
confidence: 57%
“…nasal and tracheal continuous positive airway pressure; vagotomy; laryngotracheal separation; bronchopulmonary receptors NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE (CPAP) has been used in newborns for a number of years for treating respiratory distress syndrome and apneas of prematurity and as a bridge between endotracheal tube ventilation and spontaneous ventilation (4,6,10). However, laryngeal functions, such as nonnutritive swallowing (NNS), which fulfils the important task of clearing upper airways from secretions and liquids refluxed from the stomach, have not been specifically assessed in newborns during nasal CPAP, aside from one study wherein nasal CPAP was shown to increase laryngeal opening (5).…”
mentioning
confidence: 99%
“…At histological examination, surfactant-deficient lungs have areas of atelectasis and overinflation, which could be effectively prevented by application of n CPAP shortly after birth. [8910] Therefore, early application of n CPAP may be effective in the management of RDS. Previous descriptions have been described in trials in which “early” CPAP was started at a variable period of time extending several hours after birth.…”
Section: Discussionmentioning
confidence: 99%
“…They found that in infants with birth weight less than 1000 g, the use of early n CPAP significantly reduced intubation rate, duration of ventilation and incidence of bronchopulmonary dysplasia. [10]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation